A Cationic Zinc Hydride Cluster Stabilized by an N‐Heterocyclic Carbene: Synthesis, Reactivity, and Hydrosilylation Catalysis1. Issue 48 (24th September 2014) - Rit, Arnab; Zanardi, Alessandro; Spaniol, Thomas P.; Maron, Laurent; Okuda, Jun
Abstract The trinuclear cationic zinc hydride cluster [(IMes)3Zn3H4(THF)](BPh4)2 (1) was obtained either by protonation of the neutral zinc dihydride [(IMes)ZnH2]2 with a Brønsted acid or by addition of the putative zinc dication [(IMes)Zn(THF)]2+. A triply bridged thiophenolato complex 2 was formed upon oxidation of 1 with PhSSPh. Protonolysis of 1 by methanol or water gave the corresponding trinuclear dicationic derivatives. At ambient temperature, 1 catalyzed the hydrosilylation of aldehydes, ketones, and nitriles. Carbon dioxide was also hydrosilylated under forcing conditions when using (EtO)3SiH, giving silylformate as the main product.